Aktivitas Antioksidan dan Sifat Organoleptik Teh Daun Sirsak (Annona muricata Linn.) Berdasarkan Variasi Lama Pengeringan - Delvi Adri; Wikanastri Hersoelistyorini; Agus Suyanto (Jurnal Pangan dan Gizi, 2013)
Soursop leaf has been used traditionally to treat a variety of diseases, because soursop leaf contain antioxidant compound. The research objective to be achieved is to measure and analyze the activity of antioxidant and organoleptic properties of Soursop Leaf Tea by variations in drying time 30,60, 90, 120, and 150 minutes. Measurement of antioxidant activity using UV-Vis spectrophotometry method (λ 517 nm), whereas the organoleptic parameters :  taste, color, aroma, and appearance. Result of studies that a treatment time of drying effect on antioxidant activity of Soursop Leaf Tea. Soursop leaf drying conditions at 50oC with a temperature of 150 minutes give the highest level of antioxidant activity and the lowest EC50 value, but it  has lowest a flavor organoleptic. Recommendations, dryingtemperature of 50oC tailings with drying 150 minutes, and to increase flavor can be done with the  added the essen.